The value of landscape design towards residents in housing areas in the Klang valley - Fitrynadia binti Mohd Shahli (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2015)
Landscape design becomes an exercise that can give benefit to the community. The implementation of landscape design in housing areas has become a demand in the development of the housing industry nowadays. This is due to the awareness regarding the importance values of landscape design as one of the indicators to achieve a sustainable environment has been aware of. The impact on its values such as social, environmental, aesthetic and functional values, on a community has become a priority in this study. Therefore, the aim of this study is to investigate the value of landscape design on influencing the residents in housing areas. To complete this purpose, this study employed qualitative and quantitative methods of data collection consisting of questionnaire surveys, interviews and observations conducted in housing areas within the Klang Valley. The methods of analysis used are the statistical, content and visualization analysis. The findings indicate several characteristic of landscape design values can give impact to residents of housing areas. The characteristics divided into two major aspects: i) macro, landscape designs consists of the implementation of general use of landscape design such as recreation facilities, streetscape and back lane area; and ii) micro, landscape design consists of important of yard in the compound of the house. Besides that, findings also indicate that by implementation of landscape design values in housing can contribute to significant needs such as social, environmental, aesthetic and functional for residents. It is hoped that, this study can become a contribution in promoting the importance of landscape design toward the residents' needs in a living environment. Thus, the exposure on landscape design and awareness on the importance of landscape design for creating a sustainable environment should be introduced for all residents and developers to achieve a quality of living environment. The housing built today will not only help to reshape the environment at present, but it will also be a legacy in determining the environmental quality for the future.